RETRACTED: Melatonin Attenuates Dysregulation of the Circadian Clock Pathway in Mice With CCl4-Induced Fibrosis and Human Hepatic Stellate Cells - González-Fernández, Bárbara; Sánchez, Diana I.; Crespo, Irene; San-Miguel, Beatriz; de Urbina, Juan Ortiz; González-Gallego, Javier; Tuñón, María J. (Frontiers in Pharmacology, 2018)
Dysregulation of the circadian clock machinery is a critical mechanism in the pathogenesis of fibrosis. This study aimed to investigate whether the antifibrotic effect of melatonin is associated with attenuation of circadian clock pathway disturbances in mice treated with carbon tetrachloride (CCl4) and in human hepatic stellate cells (HSCs) line LX2. Mice received CCl4 5 μL/g body wt i.p. twice a week for 4 or 6 weeks. Melatonin was given at 5 or 10 mg/kg/day i.p, beginning 2 weeks after the start of CCl4 administration. Treatment with CCl4 resulted in fibrosis evidenced by the staining of alpha-smooth muscle actin (alpha-SMA) positive cells and a significant decrease of peroxisome proliferator-activated receptor (PPARalpha expression. CCl4 led to a lower expression of brain and muscle Arnt-like protein 1 (BMAL1), circadian locomotor output cycles kaput (CLOCK), period 1-3 (PER1, 2 and 3), cryptochrome 1-2 (CRY1 and 2) and the retinoic acid-related orphan receptor (ROR)alpha. The expression of the nuclear receptor REV-ERBbetha showed a significant increase. Melatonin significantly prevented all these changes. We also found that melatonin (100 or 500 μM) potentiated the inhibitory effect of REV-ERB ligand SR9009 on alpha-SMA and collagen1 (COL1) expression and increased the expression of PPARalphain LX2 cells. Analysis of circadian clock machinery revealed that melatonin or SR9009 exposure up-regulated BMAL1, CLOCK, PER2, CRY1 and RORalpha expression, with a higher effect of combined treatment. Findings from this study give new insight into molecular pathways accounting for the protective effect of melatonin in liver fibrosis.